The First Case of Antimicrobial-Resistant Salmonella Stanley ST29 Diagnosed Secondary to Acute Cholecystitis - Wang W; Liu S; Zhang M; Chen Y; Liang Y; You S; Lv P; Xu X; Zhang F (Infection and Drug Resistance)
Wenqing Wang,1,2,* Shufen Liu,3,* Minlan Zhang,3 Yan Chen,4 Yanru Liang,1,2 Shuqi You,1,2 Peijun Lv,4 Xuebin Xu,5 Fenghua Zhang3 1Department of Microbiology, Shanghai Pudong New Area Center for Disease Control and Prevention (Shanghai Pudong New Area Health Supervision Institute), Shanghai, People’s Republic of China; 2Fudan University Pudong Institute of Preventive Medicine, Shanghai, People’s Republic of China; 3Department of Laboratory Medicine, Zhoupu Hospital Affiliated to Shanghai University of Medicine and Health, Shanghai, People’s Republic of China; 4Department of Microbiology, Panzhihua City Center for Disease Control and Prevention, Panzhihua, People’s Republic of China; 5Division of Pathogen Testing and Analysis, Shanghai Center for Disease Control and Prevention, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fenghua Zhang, Email zpyyzfh@163.comObjective: To analyze the phenotypic and genomic characteristics of a non-typhoidal Salmonella bile isolate from a patient with chronic diarrhoea secondary to acute cholecystitis.Methods: The patient presented with chronic diarrhoea lasting for two weeks, which was secondary to acute cholecystitis. The non-typhoidal Salmonella bile isolate was identified using biochemical tests, mass spectrometry, serum agglutination tests, and antimicrobial susceptibility testing. Subsequently, whole-genome sequencing (WGS) was performed to predict and annotate the serotype, multilocus sequence typing (MLST), antimicrobial resistance genes (AMR), mobile genetic elements (MGEs), and virulence genes of the isolate.Results: The isolate was identified as Salmonella spp. by biochemical tests and mass spectrometry. The serotype of the isolate identified by serum agglutination tests was consistent with WGS prediction and was identified as Salmonella Stanley (1,4,5,12: d:1,2, ST29). It was resistant to six antimicrobial agents, including ampicillin, ciprofloxacin, cefotaxime, azithromycin, trimethoprim/sulfamethoxazole, and chloramphenicol. Five major classes of antimicrobial agents, comprising a total of 14 resistance genes were screened, including β-lactam resistance genes: blaTEM-1B, blaOXA-1, and blaDHA-1; quinolone resistance gene: qnrB4 and aac(6′)-Ib-cr; macrolide resistance genes: mph(A), mph(E), and msr(E), and folate pathway inhibitor resistance genes: sul1, sul2, and dfrA14; chloramphenicol resistance genes: floR, catA2 and catB3. T57S mutation in the parC gene was detected in the quinolone resistance-determining region (QRDR). Three plasmid replicons (IncHI2/IncHI2A, IncR, IncN) and three insertion MGEs were predicted. Forty-two virulence genes were predicted, of which 25 were secretion and transporter genes, and ten were fimbrial adherence genes. Only one invasive protein-regulated gene(inv) was found in Salmonella Pathogenicity Islands 1(SPI-1), and no Typhoid toxin genes were predicted.Conclusion: The case of Salmonella Stanley ST29 isolated from a patient with diarrhoea lasting 55 days secondary to cholecystitis aligns with the characteristics of high drug resistance and relatively low virulence. This highlights the need for increased vigilance in clinical practice regarding invasive cases and the significant disease burden associated with the intestinal migration of antimicrobial-resistant Salmonella isolates.Keywords: Salmonella Stanley, acute cholecystitis, antimicrobial-resistant, whole-genome sequencing, invasive